Drug therapy and premenstrual disorders - Bonnice, Sherry, frey50 (Philadelphia : Mason Crest Publishers, 2004)
Overview of current treatments for Premenstrual syndrome (PMS) and premenstrual dysphoric disorder (PMDD).
Defining premenstrual syndrome -- History of Zoloft and Prozac -- How do SSRIs work? -- Treatment using SSRIs -- Case Studies -- Risks and side effects -- Alternative treatments for PMS.
Includes bibliographical references (p. [125]) and index.
84781
Keywords: Premenstrual syndrome -- Chemotherapy -- Juvenile literature; Premenstrual syndrome -- Alternative treatment -- Juvenile literature; Premenstrual syndrome; Premenstrual syndrome -- Treatment